ANALISIS STANDAR BELANJA UNTUK PENYUSUNAN RKA-APBD KEGIATAN PENYEDIAAN JASA PELAYANAN UMUM SKPD KOTA MAGELANG - Ghea Andriani, Farra; Aji Prakoso, Jalu; Nur Sarfiah, Sudati (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2025)
The management and preparation of regional budgets must be more realistic and transparent. In the digital era, it is hoped that it can increase transparency, control, and accountability in the administration of government to apply the principles of Good Governance in Magelang City. Regional Governments must implement the Expenditure Standard Analysis (ASB) system in accordance with laws and regulations to ensure that the budget prepared becomes more effective and efficient. This study aims to implement the Expenditure Standard Analysis (ASB) model in the Magelang City government. ASB is used as a tool to assess the reasonableness of costs related to the implementation of local government activities. This study examines the latest developments in the Government Spending Standards Analysis, with a focus on implementing more transparent and efficient spending policies. Through a data-based approach and analysis of public spending trends, this study also seeks to identify factors that affect state budget management and provide recommendations for increasing the effectiveness of government spending in the future. In this study, the data used is secondary data sourced from the Magelang City DPA-SKPD in 2023. The data analysis method uses standard expenditure analysis with a simple linear regression approach. The results of the study obtained the ASB equation for the budget for public service provision activities is Y = 207,880,619.31 - 1,915,565.97 X. Y is the total budget and X is the number of reports. There are 15 SKPDs with unreasonable budgets and 9 SKPDs with reasonable budgets.